The datafication of reproduction: time‐lapse embryo imaging and the commercialisation of IVF. (10th October 2019) - van de Wiel, Lucy
Abstract: The 21st century has witnessed the emergence of in silico reproduction alongside the familiar in vitro reproduction (e.g. IVF), as increasingly large and automatically‐generated data sets have come to play an instrumental role in assisted reproduction. The article addresses this datafication of reproduction by analysing time‐lapse embryo imaging, a key data‐driven technology for embryo selection in IVF cycles. It discusses the new forms of knowledge and value creation enabled by data‐driven embryo selection and positions this technology as a harbinger of a wider datafication of (reproductive) health. By analysing the new ways of seeing embryos with ' in silico vision, ' the 'data generativity' of developing embryos and the patenting of embryo selection algorithms, I argue that this datafied method of embryo selection may not just result in more or less 'IVF success, ' but also affects the conceptualisation and commercialisation of the assisted reproductive process. In doing so, I highlight how the datafication of reproduction both reflects and reinforces a consolidating trend in the fertility sector—characterised by mergers resulting in larger fertility chains, online platforms organising fertility care and expanded portfolios of companies aiming to cover each step of the IVF cycle.